Optimization of the Financial and Budgetary Mechanism for the Functioning of Educational Institutions of Higher Education in the Conditions of Innovative Economy Development in the Russian Federation - GUBARKOV, Sergey V.; USHATIKOVA, Irina I.; LEONTEVA, Anna A.; KORIAGINA, Kristina S. (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The management of higher education institutions’ system should be based on an understanding of their tasks and their role in the structural component of the entire social and economic state system. The article shows that currently the system of higher education in the Russian Federation is basically on state support. With all the possibilities for investing and distributing public funds to higher education institutions’, most of them are not capable to integrate quickly into the modern market operating conditions. Unfortunately, most higher education institutions’ graduates are reducing the learning process to the need only to gain the diploma which confirms qualification, but does not guarantee the existence of theoretical knowledge and practical skills. So it confirms the qualification without a sufficiently qualitative test of knowledge and practical skills. The financial and economic activity of higher education institutions’ is based on observance of formal matters according to accreditation indicators and participation of employers in the teaching process. In conditions when any knowledge becomes international and commercially integrates with production complexes, the functioning of higher education institutions should become the reason and basis for the increment of practical knowledge and occur in close cooperation with industrial structures. The subject of the research is the system of the state order for training the specialists functioning in the conditions of reforming system of higher education in the Russian Federation. The purpose of the article is the development of recommendations about the improvement of the financial budgetary mechanism of functioning the educational organizations of the higher education in the conditions of innovative economy development in the Russian Federation. Scientific novelty of work is defined in the use of new principles of educational organizations management of the higher education in the financial and economic spheres and outlines the perspectives for further integration into the world educational and economic space.